Еволюція геополітичного значення Кримського півострова - Гоцловський, А. (Історичний архів. Наукові студії, 2008)
Метою даної статті є аналіз еволюції “геополітичного потенціалу”
Кримського півострова на фоні історичних змін, які мали місце в межах
навколишнього макрореґіону. Целью данной статьи является анализ эволюции “геополитического
потенциала” Крымского полуострова на фоне исторических изменений,
которые имели место в пределах окружающего его макрорегиона. In the paper I have analyzed the geopolitical position of the Crimean
Peninsula at the background of the Black & Azov seas macro-region from the
ancient time till today. In the research I have used the elements of the concept of
the importance levels of geopolitical analyses of P.J. Taylor (1989). It has been
concluded that geopolitical importance of the Peninsula has been and continues
to be considerable, although in the individual periods of time the weights are
different. At the continental and macro-regional levels of top importance were, by
turns, trade by sea, or geo-strategic functions, what is more, in the contemporary
time – balneological & recreational functions. This activity was strongly
conditional upon geographical location and the features of natural environment of
Crimea and/or its macro-region. At the local level the greatest role was played by
the clear duality of the Peninsula and the diversity and quality of natural
environment of its hilly southern part.